Dora's chilly day - Thorpe, Kiki. (New York Simon Spotlight, 2004)
When Dora and Boots go to get Abuela some chocolate from the Chocolate Tree, they see what their friends like to do on a chilly day.
Keywords: Dora the Explorer (Fictitious character) -- Juvenile fiction; Travel -- Juvenile fiction